Facilitators and barriers to the Lean Enterprise Transformation program at the Veterans Health Administration. Issue 4 (October 2021) - Azevedo, Kathryn J.; Gray, Caroline P.; Gale, Randall C.; Urech, Tracy H.; Ramirez, Jeremy C.; Wong, Emily P.; Lerner, Barbara; Charns, Martin P.; Vashi, Anita A.
Abstract : Background: The Veterans Health Administration piloted a nationwide Lean Enterprise Transformation program to optimize delivery of services to patients for high value care. Purpose: Barriers and facilitators to Lean implementation were evaluated. Methods: Guided by the Lean Enterprise Transformation evaluation model, 268 interviews were conducted, with stakeholders across 10 Veterans Health Administration medical centers. Interview transcripts were analyzed using thematic analysis techniques. Results: Supporting the utility of the model, facilitators and barriers to Lean implementation were found in each of the Lean Enterprise Transformation evaluation model domains: (a) impetus to transform, (b) leadership commitment to quality, (c) improvement initiatives, (d) alignment across the organization, (e) integration across internal boundaries, (f) communication, (g) capability development, (h) informed decision making, (i) patient engagement, and (j) organization culture. In addition, three emergent themes were identified: staff engagement, sufficient staffing, and use of Lean experts (senseis). Conclusions: Effective implementation required staff engagement, strategic planning, proper scoping and pacing, deliberate coaching, and accountability structures. Visible, stable leadership drove Lean when leaders articulated a clear impetus to change, aligned goals within the facility, and supported middle management. Reliable data and metrics provided support for and evidence of successful change. Strategic early planning with continual reassessment translated into focused and sustained Lean implementation. Practice Implications: Prominent best practices identified include (a) reward participants by broadcasting Lean successes; (b) provide time and resources for participation in Lean activities; (c) avoid overscoping projects; (d) select metrics that closely align with improvement processes; and (e) invest in coaches, informal champions, process improvement staff, and senior leadership to promote staff engagement and minimize turnover. Abstract : Supplemental digital content is available in the text.